El sueño de los dioses y otros cuentos huicholes - Olmos, Gabriela (Artes de México, 2012)
Cuentos huicholes de México
Keywords: Mythos; Märchen; Huichol; Mexiko; Huichol mythology / Juvenile literature; Huichol Indians / Folklore / Juvenile literature; Huichol Indians / Legends / Juvenile literature; Indians of Mexico / Folklore / Juvenile literature; Tales / Mexico / Juvenile literature; Huichol mythology; Huichol Indians; Indians of Mexico; Tales; Mexico; Huicholes / Leyendas / Literatura juvenil; Huicholes / Folklore / Literatura juvenil; Mitología mexicana / Literatura juvenil; Folklore; Juvenile works; Legends; Kinderbuch